THE ROLE OF EXERCISE ON COGNITIVE PROCESSES AND NEUROPLASTICITY - Djuric, Emilija; Škrijelj, Daniel; Rašić Marković, Aleksandra (Medicinski podmladak, 2018)
During the process of evolution, human brain has developed an extraordinary characteristic of neuroplasticity, which is the capacity to change its structure and function under the influence of the external environment and experience. Numerous studies and evidence suggest beneficial effects of exercise on the brain and mental health. It is considered that exercise leads to the improvement of cognitive functions, with a particular emphasis on learning and memory. It was also found that exercise reduces the risk of developing dementia, it manifests an antidepressant effect and deflects cognitive decay in aging. This positive outcome is reflected in neurophysiological measures that showed increased prefrontal and temporal gray matter volume, decreased latency and increased amplitude of event related potentials in physically active individuals compared to sedentary controls. Even though the idea of the beneficial effects on mental health has been present for centuries, only recent studies have identified possible mechanisms that produce a synergistic positive effect. Potential neural mechanism that has been singled out is increased synthesis and release of neurotransmitters and neurotrophins, which then stimulate neurogenesis, angiogenesis and neuroplasticity. Exercise represents a potential adjuvant therapy in the treatment of neurodegenerative diseases, which not only reduces the cost of treatment, but also contributes to improving the quality of life and improving the mental health of an individual. It is therefore necessary to direct research into understanding the mechanisms by which exercise affects the brain. Key words: Exercise, Physical Activity, Cognition, Neuroplasticity, BDNF, Neurogenesis